2021
DOI: 10.3389/fphys.2020.628870
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Different Stretching Intensities on the Range of Motion and Muscle Stiffness of the Quadriceps Muscles

Abstract: Muscle strain is one of the most frequent sports injuries, having the rectus femoris (RF) muscle as the reported preferred site of quadriceps muscle strain. The decrease muscle stiffness could be an effective RF muscle strain prevention. In recent studies, a high-intensity static stretching intervention decreased passive stiffness, though no study has investigated on the effect of the different static stretching intervention intensities on quadriceps muscle stiffness. The purpose of this study was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 28 publications
6
49
0
Order By: Relevance
“…Previous studies showed that alteration in the muscle–tendon unit stiffness was correlated with the intensity of static stretching in the hamstrings 15 , 16 . However, Nakamura et al 18 reported that high-intensity static stretching (120%ROM) was not effective for a decrement in muscle stiffness of the rectus femoris because it is overly stressful. These data indicated that the effects of high-intensity static stretching may differ depending on the targeted muscles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies showed that alteration in the muscle–tendon unit stiffness was correlated with the intensity of static stretching in the hamstrings 15 , 16 . However, Nakamura et al 18 reported that high-intensity static stretching (120%ROM) was not effective for a decrement in muscle stiffness of the rectus femoris because it is overly stressful. These data indicated that the effects of high-intensity static stretching may differ depending on the targeted muscles.…”
Section: Discussionmentioning
confidence: 99%
“…To assess changes in the flexibility of the right hamstrings (dominant limb of all participants), knee extension ROM, passive torque at end ROM, and muscle–tendon unit stiffness were measured before and immediately after jack-knife stretching. The dominant leg was determined by asking the participant’s preferred leg when kicking a ball 18 . The flexibility measurements were performed without any warm-up.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations